Trends in the management and burden of alcoholic liver disease - Mathurin, Philippe (J Hepatol, 2015)
Alcoholic liver disease (ALD) is the most prevalent cause of advanced liver disease in Europe and is the leading cause of death among adults with excessive alcohol consumption. There is a dose-response relationship between the amount of alcohol consumed and the risk of ALD. The relative risk of cirrhosis increases in subjects who consume more than 25 g/day. The burden of alcohol-attributable liver cirrhosis and liver cancer is high and is entirely preventable. Health agencies should develop population-based policies to reduce the prevalence of harmful and/or hazardous alcohol consumption and foster research in this field to provide new diagnostic and therapeutic tools. Disease progression of patients with ALD is heavily influenced by both genetic and environmental factors. Non-invasive methods for the diagnosis of fibrosis have opened new perspectives in the early detection of advanced ALD in asymptomatic patients. Alcoholic hepatitis, the most severe form of ALD, carries a high short-term mortality (around 30–50% at 3 months). Corticosteroids improve short-term survival in patients with severe alcoholic hepatitis but duration of therapy should be adapted to early response. Liver transplantation is the best option for patients with severe liver dysfunction. However, alcohol relapse after transplantation remains a critical issue and drinking habits of transplanted patients need to be routinely screened.